MARSHALL CHARACTERISTICS WITH THE USE OF CEMENT FILLER AND STONE ASH IN THE MIXTURE ASPHALT CONCRETE WEARING COURSE (AC-WC) (Case Study: Ogan Ilir Regency Boundary Road-Lubuk Batang STA 26+485 to STA 27+405) - Asrullah, Asrullah; Anggrainy, Rita; Trisnawati, Ice; Suanto, Pangki (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2025)
Indonesia is experiencing significant growth in traffic loads, but this is often not balanced by the development of adequate road infrastructure. This phenomenon occurs because the growth of traffic loads is faster than the development of road infrastructure. Excessive traffic loads can cause road damage. When a road has to carry a traffic load that exceeds its planned capacity, damage will occur gradually and impact the quality of the road infrastructure. Asphalt is a dark brown or not thick hydrocarbon compound formed from the elements asphaltenes, resins, and oils. Asphalt in the pavement layer functions as a binding material between the aggregates to form a compact mixture, thus providing the strength of each aggregate. There are various asphalt mixtures, such as hot asphalt mixtures using cement filler and stone ash on the surface layer of the Asphalt Concrete Wearing Course (AC-WC). Therefore, it is necessary to carry out research to determine the Marshall characteristics in the evaluation of hot asphalt mixtures using cement filler and stone ash on the Asphalt Concrete Wearing Course (AC-WC) surface layer, which is adjusted to the 2018 Bina Marga Revision 2 specifications. It was carried out on the district border roads as an object of research. Ogan Ilir – Lubuk Batang and in the PT Laboratory. Komba Mahaka Utama Martapura Ogan Komering Ulu Timur. Marshall test results on the AC-WC mixture using 2 different types of filler, namely cement filler and stone ash filler, and the test results on the research object showed differences in the resulting Marshall characteristics. Still, all results met the requirements of the 2018 Bina Marga general specifications Revision 2.Keywords: Marshall, Asphalt Content, Filler, Asphalt Concrete Wearing Course